Effects of Different Physical Exercises on Leptin Concentration in Obese Adolescents - Ackel-D’Elia, C.; Carnier, J.; Bueno, C. R., JR.; Campos, R.M. S.; Sanches, P. L.; Clemente, A.P. G.; Tufik, S.; de Mello, M. T.; Dâmaso, A. R. (International Journal of Sports Medicine, 2014)
In order to compare the effects of leisure physical activity (LPA), aerobic training (AT) and aerobic plus resistance training (AT+RT) as part of a 6-month interdisciplinary therapy in body composition, insulin resistance and leptin concentrations in obese adolescents, 72 volunteers (n=24 in each group) ages 15–19 years were evaluated. Delta (Δ) body mass (kg) and Δ BMI (kg/m2) was different between AT and LPA groups and in AT+RT group compared to both LPA and AT groups; Δ body fat mass (kg and %) was different only in AT+RT group compared to both LPA and AT; Δ body lean mass (%) was different only in AT+RT group; Δ body lean mass (kg) was negative only in AT and positive and different from AT in AT+RT group; ΔHOMA-IR did not differ among groups; Δ leptin (ng/ml) was negative and different from LPA for both AT and AT+RT groups. In conclusion, both AT and AT+RT promoted a reduction on leptin levels, however, the adolescents subjected to AT+RT presented better results in body composition than the AT group. These results highlight the importance of associating aerobic and resistance training with nutritional and psychological approaches in the treatment of obese adolescents.
Keywords: obesity; adolescents; leptin; physical exercise